Semaphorin 3A Shifts Adipose Mesenchymal Stem Cells towards Osteogenic Phenotype and Promotes Bone Regeneration In Vivo - Xiangwei Liu; Naiwen Tan; Yuchao Zhou; Xueying Zhou; Hui Chen; Hongbo Wei; Ji Chen; Xiaoru Xu; Sijia Zhang; Guodong Yang; Yingliang Song (Stem Cells International)
Adipose mesenchymal stem cells (ASCs) are considered as the promising seed cells for bone regeneration. However, the lower osteogenic differentiation capacity limits its therapeutic efficacy. Identification of the key molecules governing the differences between ASCs and BMSCs would shed light on manipulation of ASCs towards osteogenic phenotype. In this study, we screened semaphorin family members in ASCs and BMSCs and identified Sema3A as an osteogenic semaphorin that was significantly and predominantly expressed in BMSCs. The analyses in vitro showed that the overexpression of Sema3A in ASCs significantly enhanced the expression of bone-related genes and extracellular matrix calcium deposition, while decreasing the expression of adipose-related genes and thus lipid droplet formation, resembling a BMSCs phenotype. Furthermore, Sema3A modified ASCs were then engrafted into poly(lactic-co-glycolic acid) (PLGA) scaffolds to repair the critical-sized calvarial defects in rat model. As expected, Sema3A modified ASCs encapsulation significantly promoted new bone formation with higher bone volume fraction and bone mineral density. Additionally, Sema3A was found to simultaneously increase multiple Wnt related genes and thus activating Wnt pathway. Taken together, our study here identifies Sema3A as a critical gene for osteogenic phenotype and reveals that Sema3A-modified ASCs would serve as a promising candidate for bettering bone defect repair.